2008
DOI: 10.1007/s11999-008-0188-5
|View full text |Cite
|
Sign up to set email alerts
|

Modified Transtrochanteric Rotational Osteotomy for Femoral Head Osteonecrosis

Abstract: Osteonecrosis of the femoral head is a disabling condition affecting young patients and treatment of the disease in these patients is variable. We retrospectively reviewed 39 patients (43 hips) in whom a modified transtrochanteric rotational osteotomy was performed for osteonecrosis. The minimum followup was 24 months (mean, 36.6 months; range, 24-52 months). The mean patient age was 34.3 years (range, 20-51 years). Based on the ARCO classification, 17 hips were classified as Stage II and 26 as Stage III. We p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In addition, a number of studies did not report complete data on the outcome of each hip. For example, 32 studies [3, 5, 7-9, 15, 17, 19, 23, 26, 28, 29, 33-35, 38, 40, 44-48, 52, 54-58, 60, 61, 63, 64] reported data only in terms of conversion to THA, and seven reported only in terms of progression of disease [2,4,22,30,39,42,62]. Only 15 studies reported data in terms of both conversion to THA and progression of disease [1,6,11,12,14,16,18,20,21,24,27,49,50,65,66].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a number of studies did not report complete data on the outcome of each hip. For example, 32 studies [3, 5, 7-9, 15, 17, 19, 23, 26, 28, 29, 33-35, 38, 40, 44-48, 52, 54-58, 60, 61, 63, 64] reported data only in terms of conversion to THA, and seven reported only in terms of progression of disease [2,4,22,30,39,42,62]. Only 15 studies reported data in terms of both conversion to THA and progression of disease [1,6,11,12,14,16,18,20,21,24,27,49,50,65,66].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous procedures have been proposed to treat this condition, including core decompression [1,6,18,19,24,29,47,49,58,63], vascularized grafts [3,5,7,8,20,27,28,30,39,50,61,66], and osteotomy [2,9,16,17,23,40,44,45,62]. The term ''core decompression'' represents a spectrum of procedures that may include one large core tract or multiple small tracts [25,32].…”
Section: Introductionmentioning
confidence: 99%
“…7) In the described patient, the rotation involved a movement of almost 90 degrees anteriorly, and thus, the anterosuperior osteonecrosis was relocated anteroinferiorly.…”
Section: )mentioning
confidence: 79%
“…Because the patient was young and active, modified transtrochanteric rotational osteotomy 7) was planned to preserve the femoral head (Fig. 3).…”
Section: Case Reportmentioning
confidence: 99%
“…9 We have been performing a modified transtrochanteric rotational osteotomy with good results in our center since 2003. 10 We report our experience in managing 3 cases of posttraumatic avascular necrosis of the femoral head in teenagers with a modified transtrochanteric rotational osteotomy, which has not been reported previously.…”
Section: Introductionmentioning
confidence: 94%